Biodiversity and local perceptions on the edge of a conservation area, Khe Tran Village, Vietnam - Boissiere, M.; Basuki, I.; Koponen, P.; Wan, M.; Sheil, Douglas (Center for International Forestry Research, 2006)
Decisions on land use in Vietnam are often only based on biophysical and economical assessments, with little consideration for the local people’s opinions or perspectives. This can lead to conflicts over natural resources management, unsustainable land use and decisions that are unfair to local people. In the landscape surrounding Khe Tran, a village in Central Vietnam lives a Pahy minority group. The driving force in this area has been different land use policies, resulting mainly from a government ‘top down’ approach, and the consequent changes in local forest status. The major activities for local livelihoods have shifted from swidden agriculture and high dependency on natural forests, to more sedentary activities. Khe Tran is now situated in the buffer zone of a planned nature reserve and the government has encouraged the villagers to plant economic crops in the bare hills around the village. The people’s dependence on forest resources has significantly decreased, and most of the local knowledge about natural forests may soon be lost. The main land covers around the village are now Acacia and rubber plantations, bare lands, and lands for agriculture. Local knowledge and perspectives are rarely taken into account by state institutions when implementing land allocation projects or making decisions on natural resource management and land use at the landscape level. There is opportunity to better inform development agencies and involve local level stakeholders so that more sustainable decisions can be made. This book reports on what Khe Tran villagers find important in terms of environmental services and resources in their landscape. Our approach integrates multidisciplinary activities - through human and natural sciences- and explains the relative importance of landscape components, products and species for local people. It aims to better articulate local people’s priorities for the future, their hopes and values as well as their relationship with the conservation area.